Recommendations to the development plan 2024 - 2027 of the municipality of San Antonio del Tequendama - Cundinamarca (2022)
In the vast majority of cases, the next governors and mayors, have ideas based on the search to improve in all areas, the territory they will begin to govern, in this new stage great unknowns arise, for this reason, this document will develop one of many of these concerns and is, how to ensure that the municipality of San Antonio del Tequendama - Cundinamarca, has a development plan that meets the needs of its population? It is necessary to mention that the Development Plan is a fundamental part of the planning in the Public Administration, each Development Plan for a National, Departmental and Municipal government must be key for a positive management, the Plans must not only take into account its regulations, but, in which public policies, studies, norms and experiences, are going to be supported to make a strategy that allows to make an investment that makes possible the economic development of the region, without forgetting to take into account social sectors such as health, education, culture, sports and recreation, among others. For this reason, the purpose of this document is to highlight the key issues to take into account in the realization of the next Development Plan 2024 - 2027 of the municipality of San Antonio del Tequendama - Cundinamarca, in order to prioritize actions, additionally that it is viable according to the resources that the municipality will have, implemented in a given time, also ensuring its continuity with the change of the administrative period, and finally, that it is a complete and simple Development Plan to be known and understood by the whole community. In addition to taking into account the organic law that structures the construction of development plans, other regulations will be taken into account, as well as the analysis of at least the last two development plans of the municipality of San Antonio del Tequendama, along with the agreements of approval of the budgets of each of its periods (2016 to 2022), so at the end of the process, the recommendations for the new municipal Development Plan will be made known.